العطور و أحكامھا في الفقھ الإسلامي - دراسة فقھیة مقارنة - خنفور, نجيبة (University of Eloued-جامعة الوادي, 2015)
This research treated an important aspect of man's life which is the issue "the use of parfume " according to the Islamic legislation "fiqh This research highlighted the theories related to the topic of perfume and some of the contemporary scholarsperspectives. This research tried to answer the most problematic questions suchas : The use of perfume in terms of man's perity and `impurity ` and its impact on man'sworship and his daily activities. This research concluded with some results and recommendations such as : The legislation about perfume differs according to the nature of the perfume itself and its varied usage and as a result the Islamic scholars have made different teachings. Also 'along this research` there are other results.
مذكرة ماستر
Keywords: العطور /الفقه الإسلامي / أحكامھا; Perfumes / Islamic jurisprudence / its provisions